Las hazañas de un joven don Juan - Apollinaire, Guillaume, 1880-1918 (Ediciones de Intervención Cultural/Montesinos, 2004)
This novel tells the story of the sexual awakening of the precocious Roger, during one summer at his family's chateau. His affairs include servant girls, his maiden aunt and both his sisters. It was written by the poet Guilaume Apollinaire when he was in desperate need of money.